Inovasi Teknologi dalam Sistem Informasi Akuntansi: Financial Planning pada Bisnis UMKM - Farah Qalbia; Anggelica Ramadhani (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2023)
This webinar discusses the importance of technological innovation in accounting information systems to enhance the efficiency and effectiveness of financial management among Micro, Small, and Medium Enterprises (MSMEs). By leveraging technologies such as cloud computing and integrated accounting information systems, MSMEs can improve transparency, accuracy, and speed in financial reporting, ultimately supporting better strategic planning and decision-making. The findings from this webinar reveal that many MSMEs still rely on traditional methods to assess financial health, which are inadequate to face the current economic challenges. The speakers emphasized the importance of good risk management and effective branding strategies to achieve sustainable business growth. By adopting new technologies and implementing prudent financial management, MSMEs can maintain their competitiveness in the dynamic global market.